Total synthesis of (+)-cladospolide D. Issue 4 (15th March 2016) - Reddy, Chada Raji; Dilipkumar, Uredi; Mallesh, Kathe; Latha, Bellamkonda; Shravya, Ravula
Graphical abstract: Abstract: The asymmetric total synthesis of cladospolide D, a natural 12-membered macrolide antibiotic, has been accomplished in 12-steps. Sharpless asymmetric dihydroxylation, Grubb's cross metathesis, and Shiina lactonization have been employed as the key reactions for the installation of the desired stereocenter and the construction of the macrolactone framework. Abstract : (2 R, 8 S )-8-(( tert -Butyldimethylsilyl)oxy)nonane-1, 2-diol: C15 H34 O3 Si [ α ]D 25 = +4.4 ( c 0.5, CHCl3 ) Source of chirality: ( S ) - propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (2 R, 8 S ) Abstract : (2 R, 8 S )-8-(( tert -Butyldimethylsilyl)oxy)-2-((4-methoxybenzyl)oxy)nonan-1-ol: C23 H42 O4 Si [ α ]D 20 = −1.5 ( c 1.00, CHCl3 ) Source of chirality: ( S ) - propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (2 R, 8 S ) Abstract : Ethyl (5 R, 11 S, E )-11-(( tert -butyldimethylsilyl)oxy)-5-((4-methoxybenzyl)oxy)-4-oxododec-2-enoate: C28 H46 O6 Si [ α ]D 20 = +46.8 ( c 1.07, CHCl3 ) Source of chirality: ( S ) - propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (5 R, 11 S ) Abstract : Ethyl (5 R, 11 S, E)-11-hydroxy-5-((4-methoxybenzyl)oxy)-4-oxododec-2-enoate: C22 H32 O6 [ α ]D 20 = +51.6 ( c 1.5, CHCl3 ) Source of chirality: ( S ) - propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (5 R, 11 S ) Abstract : (5 R, 11 S, E)-11-Hydroxy-5-((4-methoxybenzyl)oxy)-4-oxododec-2-enoic acid: C20 H28 O6 [ α ]D 20 = +5.0 ( c 1.25, CHCl3 ) Source of chirality: ( S ) - propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (5 R, 11 S ) Abstract : (6 R, 12 S, Z )-6-((4-Methoxybenzyl)oxy)-12-methyloxacyclododec-3-ene-2, 5-dione: C20 H26 O5 [ α ]D 20 = +45.2 ( c 0.55, CHCl3 ) Source of chirality: ( S )-propylene oxide, Sharpless asymmetric dihydroxylation Absolute configuration: (6 R, 12 S )